Identifikasi Lapisan Bawah Permukaan Untuk Analisis Potensi Longsor Di Daerah Cikidang, Kabupaten Majalengka - Silmi Afina Aliyan; Totok Doyo Pamungkas; Nanin Trianawati Sugito; Dede Rohmat; Haikal Muhammad Ihsan; Vasha Namira Adzanah; Zaenal Mahfud; Sekar Ayu Pertiwi; Raffi Razan Fulvian; Aditya Surya Erlangga (CV. Multi Kreasi Media, 2025)
The geological conditions around Bantarujeg District exhibit diverse and intriguing features, especially in the area north to northwest of Cikidang village, characterized by elongated hills and steep slopes bordering the Ciwaru River to the east. Landslide potential in this region is influenced by various factors such as soil types, rock formations, subsurface materials, water saturation, slip planes, and gravity. This research aimed to mitigate landslide risks by analyzing subsurface geological conditions and structures to identify slope slip areas and predict the depth and type of layers beneath the northwest slope of Cikidang village using the Wenner-Schlumberger 2D geoelectric method. Measurements were taken along two lines: the mainline trending NW-SE and the crossline trending NE-SW. On the mainline, the topsoil layer (5.54 - 237 Ωm) is predicted to be less than 7 meters deep, with volcanic fragments (237 - 2,893 Ωm) at depths of 7 – 9.5 meters. Layers deeper than 9.5 meters exhibit resistivity values exceeding 2,893 Ωm. On the crossline, the topsoil layer (6.40 - 261 Ωm) is also less than 7 meters deep, with volcanic breccia (261 - 1,152 Ωm) at depths of 7 – 9.5 meters. Layers deeper than 9.5 meters have resistivity values exceeding 1,152 Ωm, indicating the presence of basaltic breccia in the lower layers.